Relocating and Resizing Strategy for Shop House Area to Build Resiliency in Dealing with New Normal - Anastasia Karin; Felia Srinaga (ADI Publisher, 2020)
Covid-19 pandemic has dramatically impacted performance and demand in the retail-shopping sub-sector. All trading activities have mostly gone into online activity to comply with safety measure protocols. In the long run, this situation will impact the tourism sector as certain areas rely on the role of shop houses as their economic driver. As the new normal requires people to be able to coexist with Covid-19, many retail-shopping areas should review their strategies and work patterns. One of them is applying relocating and resizing strategies to shop houses. Relocating and resizing the shop houses means to review the spaces, reconsider open and enclosed spaces, as well as create a flexible space that prioritizes vitality in order to increase space effectiveness that is safe for shop customers and shop-owners. This research is conducted in the Pasar Lama Tangerang area and the research method is done through field observation as well as literature studies. Through this research, the authors obtain certain criteria that meet relocating and resizing strategies to increase effectiveness and improve the shop-houses’ performance to build resilience in the tourism sector.